2014
DOI: 10.1590/s0004-28032014000400005
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Endoscopic and Histological Features in Adults With Suspected Celiac Disease in a Referral Center of Minas Gerais, Brazil

Abstract: -Context -Clinical presentation of celiac disease is extremely variable and the diagnosis relies on serologic tests, mucosal intestinal biopsy and clinic and serologic response to a gluten-free diet. Objectives -To correlate the endoscopic and histological aspects of adult patients with suspicion of celiac disease and to evaluate the interobserver histological agreement. Method -Endoscopic aspects of 80 adult patients were evaluated and correlated with the histological features according the Marsh-Oberhuber cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The CD is a highly prevalent, non-communicable disease in most parts of the world, including India (prevalence=1%), that can manifest at any age and shows varied clinical presentations [ 10 ]. The proportion of typical CD is higher in children than in adults [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CD is a highly prevalent, non-communicable disease in most parts of the world, including India (prevalence=1%), that can manifest at any age and shows varied clinical presentations [ 10 ]. The proportion of typical CD is higher in children than in adults [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…With increased availability of paediatric UGI endoscopy, many endoscopies are done for reasons other than suspected CD, and the detection of suggestive endoscopic features in the duodenum can alert endoscopists to take a duodenal biopsy and aid in increasing the diagnostic rate of the disease [ 8 ]. A number of macroscopic endoscopic markers of CD have been identified and includes [ 9 10 ]: 1) Scalloping-indented aspect of duodenal folds; 2) Absence or reduction of number of duodenal folds; 3) Mosaic pattern-micro nodular look of mucosa; 4) Grooves and fissuring of mucosa; 5) Sub mucosal vascular pattern; 6) Nodularity.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of a relationship has also been reported in other studies. 34 The present study has some limitations. First of all, most of our patients had been diagnosed with celiac disease many years ago, and therefore, they probably would make mistakes in remembering their initial symptoms.…”
Section: Discussionmentioning
confidence: 81%
“…The proportion found in our study was slightly higher than Mansoor et al study. 14 Ackerman et al found that patients with celiac disease were younger, had lower mean haemoglobin levels, and had much more incidents of lengthier periods of anaemia and diarrhoea as compared to those who did not have celiac disease. 15 Another study by Grisolano et al 16 found only 8.7% with celiac disease.…”
Section: Discussionmentioning
confidence: 99%